Substandard and falsified pediatric medicines in low–middle-income countries: A narrative review on impacts and strategies - Shailee Dewan, Pradeep M. Muragundi, Vani Lakshmi Ramesh, Virendra S. Ligade, Dharmagadda Sreedhar, Adithya D. Shetty (Journal of Applied Pharmaceutical Science, 2025)
Substandard and falsified medicines (SFMs) pose a great risk to public health worldwide in low and middle-income countries. Vulnerable groups like children are disproportionately exposed. The dangerous medicines vary from useless to poisonous treatment, increase resistant microorganisms, and enhance the disease burden. SFM has led to numerous tragic events in developing countries, which is a major crime against humanity and depicts one of the most intricate safety issues in healthcare systems. This narrative review presents data from available published literature of varying scientific databases, regulatory requirements, and grey literature to compile in-depth information and concentrate on implementing strategies and initiatives for the prevention of SFM among children. The article emphasizes substandard and counterfeit antimalarial’s global effects, poor access to essential quality medicine with probable effects of substandard antibiotics, and effects of substandard analgesics and antipyretic syrup. The strategies include healthcare leadership consolidating the pharmaceutical supply chain with high-end technology, cost-effective analysis, pharmaceutical education, training and awareness, global funds, and other policies. Different organizations’ initiatives at the global level are the International Medical Products Anti-Counterfeiting Taskforce of the World Health Organization and the United Nations International Children’s Emergency Fund, both of which enhance coordination between governments, healthcare professionals, and regulatory authorities. But a multifaceted approach involving greater regulatory and enforcement efforts as well as improved healthcare access, education, and cooperation at the international level is needed to protect children.
Keywords: Pediatric drugs, substandard, falsified, potential effects, global trade